A summarized review about natural polymers role in floating drug delivery system and in-vivo evaluation studies (International Current Pharmaceutical Journal, 2017)
The approach of eco-friendly and safe environmental materials for various industrial applications like medicine, agriculture and similar areas is growing rapidly. The advantages of biologically degradable and non-toxic materials like the natural polymers are evident by the mounting level of its use in pharmaceutical field particularly. The various natural polymers have been aiding the drug delivery systems for long time as the drug transporters with the objective of improving the efficacy and efficiency. The floating drug delivery systems are required to possess proper floating capability in gastric systems and use of natural polymers in such delivery systems has been very beneficial. The physical characteristics of natural polymers facilitate them to be brilliant drug carriers for such type of drug delivery systems.  The aim of this review is to provide the overview of role of natural polymers in floating drug delivery system, its characteristic effects, ongoing research and trend of future developments and applications in the field.Javaid et al., International Current Pharmaceutical Journal, March 2017, 6(4): 23-26http://www.icpjonline.com/documents/Vol6Issue4/01.pdf